Perbaikan Sifat Mekanis Batu Bata Tanpa Dibakar dengan Campuran Limbah Karbit dan Abu Sekam Padi - Andre, Yosi; Siagian, Taufik Nugraha (Universitas Muhammadiyah Yogyakarta, 2010)
Brick is one important element in a building. Bricks are generally made by burning dry clay , and this process will emit air pollutant. In addition, the bricks that widely available on the market have a poor quality. Therefore, the quality of bricks needs to be effectively improved by means of environmentally friendly and low cost procedure. This research aims to improve the mechanical characteristics of unburnt bricks by adding a mixture of calcium carbide residue (CCR) and rice husk ash (RHA). In this study, the effect of the percentage of additive material and the proportions of CCR and RHA on the mechanical properties are studied. The results showed that the compressive strength of bricks is influenced by the content of additive material. In addition, the optimum compressive strength was found to be after 21 days of cating for all additive material, afterwhich the strength sarted to decrease. Bricks possessing the highest compressive strength are those produced with 70% additive and CCR-to-RHA ratio of 2/1. The compressive strength reached 125.91 kg/cm2 after 21 days of moulding.